MSME Business Growth in Indonesia: is the Indonesian Standard Quick Response Code (QRIS) a Major Factor? - Nita, Nurul Apri; Bangsawan, Satria; RH Pandjaitan, Dorothy (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
This research aims to analyze the relationship between the adoption of the Quick Response Code Indonesian Standard (QRIS) on the business growth of Micro, Small and Medium Enterprises (MSMEs) in the food industry sector in Indonesia. The research methodology used in this research is quantitative, using SmartPLS 3.0 software. Primary data collection was carried out by taking a sample of respondents, namely MSME actors in Indonesia. A total of 200 samples were used for this research. Data was obtained through the use of Google Form, with indicator assessment carried out using a Likert Scale. Research findings show that there is a good correlation between the Quick Response Code Indonesian Standard (QRIS) in relation to the growth of MSME businesses in Indonesia, this is because QRIS lowers the barriers to entering the digital payment ecosystem by simplifying the process and reducing setup costs which are often a barrier. for MSMEs. This directly increases their access to a wider market and has the potential to increase business income. Operational efficiency is also improved through the use of QRIS. By utilizing QRIS, MSMEs can reduce the time and resources required to manage payment transactions.